Novel lineage‐specific transmembrane β‐barrel proteins in the endoplasmic reticulum of Entamoeba histolytica. (20th May 2019) - Santos, Herbert J.; Imai, Kenichiro; Makiuchi, Takashi; Tomii, Kentaro; Horton, Paul; Nozawa, Akira; Okada, Kenta; Tozawa, Yuzuru; Nozaki, Tomoyoshi
Abstract : β‐barrel outer membrane proteins (BOMPs) are essential components of outer membranes of Gram‐negative bacteria and endosymbiotic organelles, usually involved in the transport of proteins and substrates across the membrane. Based on the analysis of our in silico BOMP predictor data for the Entamoeba histolytica genome, we detected a new transmembrane β‐barrel domain‐containing protein, EHI_192610. Sequence analysis revealed that this protein is unique to Entamoeba species, and it exclusively clusters with a homolog, EHI_099780, which is similarly lineage specific. Both proteins possess an N‐terminal signal peptide sequence as well as multiple repeats that contain dyad hydrophobic periodicities. Data from immunofluorescence assay of trophozoites expressing the respective candidates showed the absence of colocalization with mitosomal marker, and interestingly demonstrated partial colocalization with endoplasmic reticulum (ER) proteins instead. Integration to organellar membrane was supported by carbonate fractionation assay and immunoelectron microscopy. CD analysis of reconstituted proteoliposomes containing EHI_192610 showed a spectrum demonstrating a predominant β‐sheet structure, suggesting that this protein is β‐strand rich. Furthermore, the presence of repeat regions with predicted transmembrane β‐strand pairs in both EHI_192610 and EHI_099780, is consistent with the hypothesis that BOMPs originated from the amplification of ββ‐hairpin modules, suggesting that the two Entamoeba‐ specific proteins are novel β‐barrels, intriguingly localized partially to the ER membrane. Abstract : Our β‐barrel outer membrane proteins (BOMP) predictor detected two candidates, EHI_192610 and EHI_099780, in Entamoeba histolytica . Microscopy analyses showed unexpected partial colocalization with endoplasmic reticulum (ER) markers. CD data suggest EHI_192610 is β‐strand rich. Both candidates possess predicted transmembrane β‐strand pairs, consistent with the hypothesis that BOMPs originated from ββ‐hairpin module amplification, suggesting they are novel β‐barrels intriguingly localized partially to the ER membrane.